Comparison of womwne's quality of life post abdominal and vaginal hysterectomy - Fauzan F; Bobby Indra Utama; Firdawati Firdawati (Universitas Andalas, 2022)
Introduction:Hysterectomy is the most common major surgical procedure in gynecology. Approximately 90% of hysterectomies are performed on indications of benign gynecological disease. The number of women affected by hysterectomy is relatively low, but the impact of these complications often changes the quality of life. There are several types of hysterectomy, from partial/supravaginal, complete/total, to radical. Hysterectomy with any surgical technique can cause complications. This can be minimized by careful surgical planning and preparation before surgeryAssessing changes in quality of life after surgery is important for patient decision making and for health care evaluation, as health care becomes more standardized. Objective: This study aims to determine the difference in quality of life between women who have undergone abdominal hysterectomy surgery and women who have undergone vaginal hysterectomy surgery.Methods: This research is an analytic observational study with a cross sectional comparative study approach which was conducted on 54 women who had undergone hysterectomy at Dr. RSUP. M. Djamil, Padang. 27 of them underwent abdominal hysterectomy, and 27 others underwent vaginal hysterectomy. All patients were interviewed using the Short Form-36 (SF-36) questionnaire. The assessment is carried out with a scoring system where a score of 0 is the lowest value, and 100 is the highest value.Results: The average quality of life of the woman's post abdominal and vaginal hysterectomy was 91.71 ± 6.73 and 99.07 ± 1.66 respectively. There is a difference in the mean value of quality of life of women and post abdominal and vaginal hysterectomy (p<0.05).Conclusion: There was a significant difference between the quality of life of women after hysterectomy, where women who underwent vaginal hysterectomy had a higher quality of life than women who underwent abdominal hysterectomyKeywords: Hysterectomy, Abdominal, Vaginal, Quality of life